Clarithromycin induced Stevens-Johnson syndrome in the oral cavity: Case report - Zisis Vasileios; Zisis Stefanos; Poulopoulos Konstantinos; Shinas Nikolaos; Papadopoulos Petros; Charisi Christina; Kyriakou Nikolaos; Cordahi Joe; Poulopoulos Athanasios (Balkan Journal of Dental Medicine)
Background/Aim: Macrolides belong to the very often used antibiotics. However, macrolides are recognized as antibiotics that are possibly linked to the development of Stevens-Johnson syndrome (SJS) and Toxic Epidermal Necrolysis (TEN). SJS and TEN (SJS/TEN) are uncommon, life-threatening, and potentially fatal hypersensitivity mucocutaneous reactions that may affect the oral mucosa as well. The aim of this case report refers to illustration of the macrolide induced SJS in a 58-years-old male patient. Case Report: A 58-years-old male patient presented himself, as a medical emergency to our clinic, reporting acute, severe, radiating pain and a burning sensation on the whole surface of the oral cavity, including the maxilla, the mandible, the tongue, the cheeks as well as both the hard and the soft palate. The clinical examination revealed hemorrhagic erosions and erythematous macules. His medical history was reviewed in detail with no underlying health issues; however, the patient mentioned the intake of clarithromycin, 500 mg twice daily, due to acute sinusitis, starting the night prior the appearance of the initial symptoms. The diagnostic procedure came up to SJS and methylprednisolone was prescribed. After ten days, the patient reported that the pain had receded almost totally, and the wound healing was complete. Conclusions: An extensive recent review on macrolide induced SJSs revealed 7 cases attributed to clarithromycin. Identifying the responsible agent may be easy in cases where the patient receives only one drug, as in our case. Case reports act as early warnings for potential issues uprising public awareness of the putative link and subsequently stimulating larger series. This patient's presentation and literature review gives a valuable contribution to the range of clinical features of SJS/TEN patients related to treatment with macrolide antibiotics, which may assist in better understanding and management of these potential complications.